Optimising the analysis of stroke trials - Gray, Laura Jayne (2008)
Most large acute stroke trials have shown no treatment effect. Functional outcome is routinely used as the primary outcome in stroke trials. This is usually analysed using a binary analysis, e.g. death or dependency versus independence. This project assessed which statistical approaches are most efficient in analysing functional outcome data from stroke trials.